You can do it too The 20 essential things every budding entrepreneur should know - Bridge, Rachel (London,Uk Kogan Page, 2009)
You can do it too is a fascinating new book wich brings together the collective knowledge and wisdom of successful entrepreneurs in the form of 20 essential elements to focus on when starting up a business
"The sunday times"
12
Keywords: Business ethics; Job stress; Labor; Teams in the work place; Work environment; Work ethic